Reforma agrária e hegemonia político cultural: da luta pela terra à conquista do poder político na Zona da Mata da Paraíba - Ramos, Marcella Arbia Ramalho (2003)
The present work intends to verify the extent to which the creation of rural settlements, built from a history of struggling, and marked by the acting of a range of social movements, contributed to the construction of a cultural-political hegemony of workers, capable of modifying the local political power. This is a case-study, concerning two towns of the region known as Zona da Mata of the state of Paraiba: Cruz do Espírito Santo and Pedras de Fogo, both with a large presence of settled areas. From the understanding that the cultural-political hegemony would show in its development the necessity of occupying the local political positions, the council elections of 2000 were taken as a reference point. To that end, three main aspects were examined: the acting of social movements, that of political parties and the perception of the process by the social actors involved. The theoretical landmark which oriented this work was represented by the categories of Hegemony and State en Gramsci, confronted with the interviews which were carried out and the elections' result. It was concluded that the seizure of land by means of struggle doesn't always lead to the construction of a cultural and political hegemony by the workers.